Network Centric Warfare (NCW)-Based Defense Policy Strategy for Addressing Asymmetric Threats - Sembiring, Heriyanta; Supriyadi, Asep Adang; Ghazalie, Ghazalie (Jurnal Ilmiah Global Education, 2025)
This study explores the strategic transformation of national defense policy through the implementation of Network-Centric Warfare (NCW) in addressing asymmetric threats. As modern warfare evolves with the rise of cyber operations, hybrid threats, and unconventional tactics, traditional military doctrines are increasingly inadequate. NCW, characterized by real-time intelligence sharing, high-speed communication networks, and AI-powered decision-making systems, offers a paradigm shift that enhances situational awareness, operational efficiency, and strategic agility. Through a qualitative analysis of theoretical and empirical studies, the research identifies the core benefits of NCW, including improved interoperability, decentralization of command, and enhanced battlefield precision. However, the study also reveals significant challenges such as cyber vulnerabilities, interoperability gaps, and ethical concerns surrounding autonomous systems. To address these issues, the paper recommends a comprehensive defense policy reform that includes robust cybersecurity infrastructure, cross-sector collaboration, human capital development, and standardized operational protocols. The findings underscore that NCW is not merely a technological upgrade but a foundational change in military doctrine, essential for ensuring strategic superiority and resilience in an increasingly complex global security landscape.